O Espaço Florestal de Alcobaça nos séculos XVIII e XIX - Maduro, António (2010)
At the beginning of the 18th century the deforestation in Alcobaça manors is intensified. The primitive broadleaved forest of Serra dos Candeeiros is cleared for the extensive olive plantations. On the other hand, the pine forest starts to expand on the sea border providing wood and timber and protecting the corn and rice fields from the sea winds and dune advance. Liberalism contributed to reduce the area and change the exploitation system of the woods, thus endangering their sustainability.